High androgen receptor mrna expression is associated with improved outcome in patients with high-risk non-muscle-invasive bladder cancer - Sikic, Danijel; Taubert, Helge; Wirtz, Ralph M.; Breyer, Johannes; Eckstein, Markus; Weyerer, Veronika; Kubon, Jennifer; Erben, Philipp; Bolenz, Christian; Burger, Maximilian; Hartmann, Arndt; Wullich, Bernd; et al. (Life, 2021)
The role of the androgen receptor (AR) in non-muscle-invasive bladder cancer (NMIBC) remains controversial. We retrospectively analyzed the mRNA expression of AR using RT-qPCR in 95 patients with high-risk NMIBC treated with a bladder-sparing approach and correlated AR with clinical data and recurrence-free survival (RFS), cancer-specific survival (CSS), and overall survival (OS). The mRNA expression of AR and KRT5, i.e., the basal-like subtype, was strongly correlated (rs = 0.456; p < 0.001). AR (p = 0.053) and KRT5 (p = 0.029) mRNA expression was negatively correlated with tumor grade. Kaplan–Meier analyses indicated significantly prolonged CSS (p = 0.020) and OS (p = 0.015) and a trend towards longer RFS (p = 0.051) in patients with high AR expression. High KRT5 expression was associated with significantly longer RFS (p = 0.033), CSS (p = 0.029) and OS (p = 0.030), while high KRT20 expression was associated with reduced RFS (p = 0.042). In multivariable analysis, none of the molecular markers was an independent prognostic factor. When performing a substratification with regard to molecular markers and clinicopathological parameters, high AR expression showed improved OS in patients with high KRT20 mRNA expression (p = 0.041). Women showed significantly longer OS in cases with high AR expression (p = 0.011). High AR was associated with significantly improved CSS in males (p = 0.044) and patients with instillation therapy (p = 0.040), while OS was improved regardless of instillation therapy. Younger patients with high AR expression had significantly improved RFS (p = 0.021), CSS (p = 0.014) and OS (p = 0.007). RFS was also improved in patients with high AR and low expression of either KRT5 (p = 0.003) or KRT20 (p = 0.014), but not in patients with high expression of KRT5 or KRT20. In conclusion, high AR mRNA expression is correlated with KRT5 mRNA expression and is associated with an improved outcome in high-risk NMIBC.
CRIS-Team Scopus Importer:2021-07-30
Keywords: Androgen receptor; Bladder cancer; KRT20; KRT5; MRNA; NMIBC; PCR